THE EFFECT OF CAPITAL STRUCTURE AND FINANCIAL STRUCTURE ON FIRM PERFORMANCE (An Empirical Study of The Financial Crisis 2008 and 2009 in Indonesia) - Ansca, Cressya Cesia; Suyapto, Kevin Agriya; Pranoto, Titin; Gunawan, Vania Pradipta (Jurnal Akuntansi dan Keuangan Indonesia, 2019)
This research aims to identify the impact of capital structure on Indonesian firms’ performance, particularly on the magnitude of impact at the period prior to crisis, crisis, and the period following the crisis that happened in 2008. The Global Financial Crisis grants a chance to scrutinize the impact of crisis between capital structure and firm performance. Proxies used for capital structure are total debt to total assets, short-term debt to total assets, and long-term debt to total assets ratio. Moreover, firm performance is measured by accounting performance (Return on Asset and Return on Equity) and market performance (Price to Equity Ratio and Tobin’s Q). Samples used include all firms listed in Indonesia Stock Exchange (IDX) from the period 2004 up to 2017, excluding financial sector firms. This research posits that capital structure generally impacts firm performance negatively. The Global Financial Crisis (GFC) that happened in 2008 serves a greater negative impact of capital structure to firm performance than it is before and after crisis. This research is intended for use by firms as a perusal in managing its capital structure, for creditors in managing its lending, and for investors in investing, prominently in times of financial crisis.